حق المعتدة من الطلاق في النفقة والسكن في الشريعة الإسلامية والقانون العراقي - المالكي، هناء هاشم عباس; كرجي، رضا محمد; البدري، حارث علي إبراهيم (الجامعة المستنصرية - كلية التربية الأساسية, 2022)
إن موضوع البحث يدور حول قضية النفقة والمسكن للمرأة المعتدة من طلاق، فالمسكن هو حاجة ضرورية ملحة للزواج، حيث يجد فيه الزوجين الراحة والطمأنينة والسكينة وفيه يستطيع كل منهما قضاء حاجاتهما الدنيوية بستر بعيدا عن أعين الناس، والسكنى للزوجة على زوجها واجبة، وهذا باتفاق الفقهاء، لأن الله تعالى جعل للمطلقة الرجعية السكنى مع زوجها، فوجوب خلال فترة العدة، وكذلك لا تعتبر الزوجة ناشزة عن طاعة زوجها شرعا وقانونا إن لم يكن هناك مسكن شرعي معد لها من قبل الزوج، والسكنى للزوجة جزء من النفقة الواجبة لها على زوجها حسبما قال الفقهاء، وجاء في المادة (الخمسون) من قانون الأحوال الشخصية العراقي باستحقاق المطلقة نفقة في العدة ونص القانون رقم (77) لسنة 1983 حق المطلقة للسكنى حتى بعد انتهاء العدة، حيث نصت المادة الثانية بأن للزوجة المطلقة السكنى لمدة ثلاث سنوات ولا بدل، ولها الحق بإقامة الدعوى مع دعوى الطلاق والتفريق، ولا يجوز إقامة دعوى مستقلة للمطالبة به، وعلى المحكمة أن تحكم بحق السكنى إذا ما توفرت شروطه، وأن حق المطلقة في السكنى لمدة ثلاث سنوات لا أساس له من الناحية الشرعية بتاتا. The topic of the research revolves around the issue of alimony and housing for a woman who is in iddat after divorce, as housing is an urgent necessity for marriage, in which the spouses find comfort, tranquility and tranquility, and in which each of them can fulfill their worldly needs in a veil away from the eyes of people, The residence of the wife over her husband is obligatory, and this is by the agreement of the jurists, because God Almighty has made the residency of the divorced woman with her husband, so it is obligatory during the waiting period, and also the wife is not considered disobedient to her husband legally and legally if there is no legal residence prepared for her by the husband, And housing for the wife is part of the alimony that is obligatory for her on her husband, according to the jurists, Article (50) of the Iraqi Personal Status Law states that the divorced woman is entitled to maintenance in the waiting period, and Law No. (77) of 1983 stipulates the right of the divorced woman to reside even after the waiting period ends, Where the second article stipulates that the divorced wife has a residence for a period of three years and no allowance, It has the right to file a lawsuit with a lawsuit for divorce and separation, and it is not permissible to file a separate lawsuit to claim it, The court must rule on the right to housing if its conditions are met, and that the divorced woman’s right to housing for a period of three years is completely unfounded from a legal point of view.
Keywords: الشريعة الإسلامية -- أحكام الطلاق -- أحكام النفقة -- عدة المطلقة -- الفقه الإسلامي